A comparative study of MPPT strategies and a novel singlephase integrated buck-boost inverter for small wind energy conversion systems - Peña, José C.U. [UNESP]; De Brito, Moacyr A.G. [UNESP]; E Melo, Guilherme de A. [UNESP]; Canesin, Carlos A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2011)
This paper presents the analysis of some usual MPPT (Maximum Power Point Tracking) strategies intended for small wind energy conversion (up to 1kW) based on permanent magnet synchronous generators (PMSG), considering the stand-alone application for a novel buck-boost integrated inverter. Each MPPT method is analytically introduced and then it is simulated using MatLab/Simulink considering standard conditions of wind and also commercially available turbines and generators. The extracted power in each case is compared with the maximum available power, so the tracking factor is calculated for each method. Thus, the focus is on the application to improve the efficiency of stand-alone wind energy conversion systems (WECS) with battery chargers and AC load supplied by inverter. Therefore, for this purpose a novel single phase buck-boost integrated inverter is introduced. Finally, the main experimental results for the introduced inverter are presented. © 2011 IEEE.
Keywords: Integrated Buck-Boost Inverters; MPPT for small WECS; Renewable Energy Sources; Small WECS with PMSG; Wind Energy; AC load; Battery chargers; Buck boost inverter; Buck-boost; Comparative studies; Integrated inverter; MATLAB /simulink; Maximum available power; Maximum Power Point Tracking; Permanent magnet synchronous generator; Renewable energy source; Single phase; Standalone applications; Standard conditions; Wind energy conversion system; Electric inverters; Energy conversion; Integration; Power electronics; Synchronous generators; Wind power